Alkali Digestibility Pattern, Apparent Solubility and Gel Consistency of Milled Rice - Maniñgat, C.C.; Juliano, Bienvenido O. (Wiley, 1978)
Analysis of milled rice samples differing in alkali digestibility pattern, apparent solubility on cooking, and gel consistency showed that the alkali digestibility pattern is not a reliable indicator for differentiating indica and japonica rices. Apparent solubility was shown to be better related to amylose content than to alkali digestibility pattern, but hard gel‐consistency samples had lower solubility values and hotwater soluble amylose than other high amylose rices. The samples with hard gel consistency also had alkali digestibility pattern B. The KOH concentration of 1.7% was verified as the most sensitive for initial screening of rices differing widely in gelatinization temperature.